Alcoholics Anonymous Comes to Poland: The Founding of the Polish AA and the American Connection - Marek Jannasz (European Journal of American Studies)
The goal of this article is primarily to present a historical outline of the origins of the Polish AA, supplemented with general reflections on the 12-step fellowships and their “American” specificity, as well as the challenges posed by their adaptation to a different cultural context. In-depth interviews used in my research, complemented by cultural sources and fellow-alcoholics' publications on the history of the community in Poland make it possible to close the gap that has persisted in the AA research. They indicate the social and cultural aspects of the spread of the 12-steps movements, which so far have not been studied directly, since the research has mainly dealt with the therapeutic side of the issue. Moreover, including the Polish perspective might add new threads to the debate on the U.S. cultural influence abroad.